Dynamic Mechanical Properties and Energy Dissipation Analysis of Sandstone after High Temperature Cycling - Qi Ping; Chuanliang Zhang; Hongjian Sun; Xu Han (Shock and Vibration)
In order to study the effect of high temperature cycling on the physical and mechanical properties of rock materials, a box-type resistance furnace was used to conduct high temperature cycling at 400°C 10 times on sandstone specimens in coal mine, and the impact compression tests under 8 loading rates were carried out using a split Hopkinson bar (SHPB) device. Results showed that, with the increase of cycle times, the gray white sandstone specimen gradually showed reddish brown spots, and the volume of specimen increased, while the mass, density, and longitudinal wave velocity decreased; in addition, the volume increase rate, the mass decrease rate, the density decrease rate, and the longitudinal wave velocity decreased rate with cycle times showed quadratic function relationship. The dynamic compressive stress-strain curve of sandstone specimens subjected to high temperature cyclic action under impact load was obviously different from that under normal temperature. The dynamic elastic modulus was obviously larger than that under static load. The failure mode of dynamic and static specimens showed brittleness and ductility characteristics, respectively. In the SHPB test, the impact pressure, reflected energy, transmitted energy, and absorbed energy of the rock specimen all increased linearly with the increase of incident energy. The dynamic compressive strength, elastic modulus, and strain rate of sandstone specimens were positively correlated with the incident energy, while the dynamic strain showed negative correlation.